Phylogenetic relationships and the evolution of host preferences in the largest clade of brood parasitic bees (Apidae: Nomadinae) - Sless, Trevor J.L.; Branstetter, Michael G.; Gillung, Jessica P.; Krichilsky, Erin A.; Tobin, Kerrigan B.; Straka, Jakub; Rozen, Jerome G.; Freitas, Felipe V.; Martins, Aline C.; Bossert, Silas; Searle, Jeremy B.; Danforth, Bryan N. (Molecular phylogenetics and evolution, 2022)
[Display omitted] •UCEs allow taxon-rich and genome-wide phylogenetic study of brood parasitic Apidae.•An expanded concept of Nomadinae includes almost all parasitic apids.•Paraphyletic Osirini split into three tribes, including newly described Parepeolini.•Trend towards increasingly unrelated and diverse hosts over time.•Early nomadines parasitized related taxa before expanding diversity of hosts. Brood parasites (also known as cleptoparasites) represent a substantial fraction of global bee diversity. Rather than constructing their own nests, these species instead invade those of host bees to lay their eggs. Larvae then hatch and consume the food provisions intended for the host’s offspring. While this life history strategy has evolved numerous times across the phylogeny of bees, the oldest and most speciose parasitic clade is the subfamily Nomadinae (Apidae). However, the phylogenetic relationships among brood parasitic apids both within and outside the Nomadinae have not been fully resolved. Here, we present new findings on the phylogeny of this diverse group of brood parasites based on ultraconserved element (UCE) sequence data and extensive taxon sampling with 114 nomadine species representing all tribes. We suggest a broader definition of the subfamily Nomadinae to describe a clade that includes almost all parasitic members of the family Apidae. The tribe Melectini forms the sister group to all other Nomadinae, while the remainder of the subfamily is composed of two sister clades: a “nomadine line” representing the former Nomadinae sensu stricto, and an “ericrocidine line” that unites several mostly Neotropical lineages. We find the tribe Osirini Handlirsch to be polyphyletic, and divide it into three lineages, including the newly described Parepeolini trib. nov. In addition to our taxonomic findings, we use our phylogeny to explore the evolution of different modes of parasitism, detecting two independent transitions from closed-cell to open-cell parasitism. Finally, we examine how nomadine host-parasite associations have evolved over time. In support of Emery’s rule, which suggests close relationships between hosts and parasites, we confirm that the earliest nomadines were parasites of their close free-living relatives within the family Apidae, but that over time their host range broadened to include more distantly related hosts spanning the diversity of bees. This expanded breadth of host taxa may also be associated with the transition to open-cell parasitism.